Online community impact to reduce diaper waste in Indonesia (study case at mamaberclodi community) - Dewi Arum Melati; Fira Nadlratan Na'im (Institute for Advanced Science Social, and Sustainable Future, 2023)
Indonesia is listed as the fifth biggest country with the biggest number of populations in the world population review with a population of approximately 275.7 million people. Indonesia also has high fertility rate which signifies a high demand in the market for meeting the production needs of diapers. Disposable diapers are one of the most purchased items by parents in general, yet they are also one of the most environmentally damaging waste products. Despite the fact that reusable diapers exist, consumer demand for disposable diapers is still rising. The prevalence of global issues and discussions regarding pollution and waste generation has received responses from various sectors of society, leading to the formation of movements and communities focused on environmental awareness. Mamaberclodi is an online community based for all mothers who use modern cloth diapers (clodi) for their children and the community pioneer who gives cloth diapers class online and free. In this article, we will explore the impact of Mamaberclodi as online communities on the issue of diapers waste in Indonesia. This research uses a qualitative approach which uses concurrent embedded design mixed method that combines qualitative and quantitative analysis. The qualitative analysis uses data from literatures review and depth interview, while the quantitative analysis uses Mamaberclodi data from their internal survey. Qualitative analysis is used to analyze interview data. Quantitative analysis uses statistical descriptive analysis to describe the data. This research provides the data from literature review, interviews from four informants, and Mamaberclodi internal data to conclude how this online community impacted the reduction of diaper waste in Indonesia. This research concludes that online communities, such as Mamaberclodi are needed to reduce the amount of waste generated. However, further research with more data is needed to support this research.